Can requirement for blood transfusion be predicted before delivery? Analysis of risk factors for blood transfusion in patients with postpartum hemorrhage - Fikret Salık; Mustafa Bıçak (IMR Press, 2021)
Background: The most frequent cause of maternal deaths in developing countries is severe postpartum hemorrhage. We aimed to determine the risk factors affecting blood and/or blood product transfusion in patients with postpartum hemorrhage who were admitted to intensive care unit and to reveal clinical outcomes. Methods: After local ethics committee approval, this retrospective study included patients monitored due to postpartum hemorrhage in the 2nd stage intensive care between 1 January 2019-1 January 2020. Patients were divided into two groups as those requiring transfusion (n = 156) and those not requiring transfusion (n = 162). Patients data such as age, blood group, pregnancy week, gravida, parity, previous cesarean history, maternal comorbidity were recorded. The form of delivery, trial of labor, cesarean type, indications, anesthesia type, multiple pregnancy, placental anomalies and predelivery hemoglobin were noteded. The amount of blood products used were identified. Results: High parity (P = 0.002), normal vaginal delivery rate (P < 0.001), primary cesarian delivery (P < 0.001), pre-delivery maternal comorbidity rate (P < 0.001) and low prepartum blood hemoglobin levels (P < 0.001) were statistically significant factors for transfusion. The rates of those with trial of labor, instrumental delivery, intrauterine fetal death, emergency cesarean and general anesthesia were high in blood transfusion group (P values 0.018, 0.024, 0.015, 0.001 and <0.001 respectively). In multivariate logistic regression analysis, positive correlations were identified between parity (aOR: 0.258), gravida (aOR: 1.452) and general anesthesia (aOR: 3.113) with postpartum blood transfusion. Antenatal hemoglobin level (aOR: 0.506) had negative correlation with blood transfusion. Conclusions: Among patients with postpartum hemorrhage, we were able to identify risk factors which predispose peripartum blood transfusion and developed a prediction model with good discrimination.